2021
DOI: 10.1057/s41282-021-00236-2
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic paranoia: Toward a reparative practice of the global psyche

Abstract: The COVID-19 pandemic has produced a collective paranoia which is not only driven by our psychic anxiety but also mirrors the irrationality of the crisis and the failure of global governance. During such catastrophic times, in which the state has failed to create a sustainable civil society, scholars such as Melanie Klein, Silvan Tomkins, and Eve Sedgwick have theorized the ways in which we may turn paranoia away from its destructive tendency toward a reparative practice of relationship-building and collective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Past research, in general, has also found evidence that individuals in high fear-inducing situations are more like to develop state paranoia (Freeman et al, 2002; Knight, 2000). Recent research has also unveiled some evidence that the spread of the global COVID-19 pandemic caused paranoid cognitions to grow worldwide (Liu, 2021; Lyons et al, 2023). In line with the empirical literature on fear and paranoia, our overarching theory, and recent evidence, we believe that as individuals experiencing a demanding situation such as fear of COVID-19 worry about getting the deadly virus, these individuals will be constantly on guard and search for information regarding the virus; they will be unable to stop themselves from thinking about the virus and will be distrustful toward others’ motives who communicate any evidence or data regarding the virus.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Past research, in general, has also found evidence that individuals in high fear-inducing situations are more like to develop state paranoia (Freeman et al, 2002; Knight, 2000). Recent research has also unveiled some evidence that the spread of the global COVID-19 pandemic caused paranoid cognitions to grow worldwide (Liu, 2021; Lyons et al, 2023). In line with the empirical literature on fear and paranoia, our overarching theory, and recent evidence, we believe that as individuals experiencing a demanding situation such as fear of COVID-19 worry about getting the deadly virus, these individuals will be constantly on guard and search for information regarding the virus; they will be unable to stop themselves from thinking about the virus and will be distrustful toward others’ motives who communicate any evidence or data regarding the virus.…”
Section: Theory and Hypothesesmentioning
confidence: 99%